2020
DOI: 10.1111/jcpe.13327
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different periodontal risk assessment methods with regard to their agreement: Periodontal risk assessment versus periodontal risk calculator

Abstract: This is an open access article under the terms of the Creative Commons Attribution NonCommercial License which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…PRA calculation was based on six parameters as previously described: (a) percentage of BOP, (b) number of residual PPD ≥ 5 mm, (c) tooth loss due to periodontitis, (d) BL/age considering the worst site affected, (e) systemic (diabetes) or genetic factors, and (f) environmental factor (smoking status) [ 16 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PRA calculation was based on six parameters as previously described: (a) percentage of BOP, (b) number of residual PPD ≥ 5 mm, (c) tooth loss due to periodontitis, (d) BL/age considering the worst site affected, (e) systemic (diabetes) or genetic factors, and (f) environmental factor (smoking status) [ 16 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, they could help to optimize clinical decision making and improve oral health [ 14 ]. In periodontology, scoring tools, such as the Periodontal Risk Calculator (PRC) [ 15 ], Perio Risk [ 14 ], the Periodontal Risk Assessment (PRA) [ 16 ], and their modifications, have been developed and evaluated for a long time [ 13 , 17 ]. The reliability of each of these tools has been demonstrated for predicting tooth loss [ 14 , 17 , 18 , 19 , 20 , 21 ] and/or periodontitis recurrence/progression [ 20 , 22 ] during the long-term periodontal follow-up, and they are mainly used to adapt periodontal maintenance frequencies at the end of active periodontal therapy [ 13 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies showed low levels of inter‐model categorical agreement when comparing class hierarchy from different PRATs. 33–35 The frequency occurrence of each group category can be appreciated in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this, the prognostic tool described in this study attempts to assess the risk for tooth loss in periodontally compromised patients at the beginning of treatment in order to support treatment planning. Furthermore, the two periodontal risk assessment methods (PRA and PRC) do not seem to have a high level of agreement in terms of patient’s individual risk for disease progression [ 44 ].…”
Section: Discussionmentioning
confidence: 99%